Behaviors of consumers, physicians and pharmacists in response to adverse events associated with dietary supplement use - Chiba, Tsuyoshi (Nutr J, 2017)
BACKGROUND: The prevalence of dietary supplements has increased in Japan, and, as a consequence, the adverse events associated with dietary supplement use have become more prominent. Severe adverse events must be reported to the Japanese government via public health centers. However, the number of cases reported to the Japanese government is limited. To clarify this discrepancy, we conducted an internet questionnaire, and surveyed how consumers, physicians and pharmacists acted when they or their patients developed adverse events due to dietary supplement use. METHODS: This study was completed by 2732 consumers, 515 physicians, and 515 pharmacist via internet surveillance on November 2015. RESULTS: Although 8.8% of consumers developed adverse events including diarrhea, constipation, stomachache, headache, and nausea and vomiting, most of them did not report their adverse events to public health centers. However, some consumers went to hospitals because of adverse events. We also surveyed how physicians and pharmacists acted when their patients developed adverse events due to dietary supplement use. Most physicians and pharmacists did not report these cases to public health centers because they were unable to definitively prove the cause-and-effect relationship of these adverse events. Furthermore, some physicians and pharmacists did not know how or where to report these adverse events. CONCLUSIONS: We clarified the reasons for the limited number of reports of adverse events to the Japanese government in this survey. It is important to encourage not only consumers, but also physicians and pharmacists to report adverse events to public health centers. In addition, an analyzing tool of cause-and-effect relationships might be helpful for physicians and pharmacists. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12937-017-0239-4) contains supplementary material, which is available to authorized users.